2019
DOI: 10.1200/jco.2019.37.7_suppl.666
|View full text |Cite
|
Sign up to set email alerts
|

The impact of PBRM1 mutations on overall survival in greater than 2,100 patients treated with immune checkpoint blockade (ICB).

Abstract: 666 Background: PBRM1 is the second most commonly mutated gene in clear cell renal cell carcinoma (ccRCC). We have previously shown favorable outcomes in PBRM1-mutated ccRCC tumors treated with vascular endothelial growth factor (VEGF) inhibitors. Recent data suggested PBRM1 mutations may sensitize ccRCC and non RCC malignancies to ICB therapy. We queried the impact of PBRM1 loss on overall survival (OS) across 2,152 patients treated with ICB. Methods: PBRM1 mutations were assessed in metastatic ccRCC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…10 However, in a larger cohort of patients with mRCC, PBRM1 loss was not associated with improved OS (HR 1.37; 95% CI 0.79 to 2.4, p=0.265). 36 Similarly, our results found that PBRM1 mutation did not predict immunotherapy responses.…”
Section: Genetic Profilingsupporting
confidence: 60%
“…10 However, in a larger cohort of patients with mRCC, PBRM1 loss was not associated with improved OS (HR 1.37; 95% CI 0.79 to 2.4, p=0.265). 36 Similarly, our results found that PBRM1 mutation did not predict immunotherapy responses.…”
Section: Genetic Profilingsupporting
confidence: 60%
“…PBRM1 loss was previously linked to better ICB response in ccRCC 20,21 . Several additional studies failed to find an association between functional PBRM1 loss and clinical benefit from immunotherapy 5,22,23 . In our study, further analysis of patients from the IMmotion150 trial treated with anti-PD-L1 or plus bevacizumab revealed a decreased response rate in tumors with PBRM1 mutations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PBRM1 mutations were reported to be associated with clinical benefit from anti-PD-1 therapy in ccRCC patients who received prior antiangiogenic therapy 20,21 . However, other contemporary studies failed to indicate PBRM1 mutations were a positive predictive biomarker for response to ICB 5,22,23 . It was reported that Pbrm1-deficient murine B16F10 melanomas were more immunogenic and more responsive to immunotherapy 24 .…”
mentioning
confidence: 97%
“…Together, these results suggest that the allele-specific effect of rs4903064 could be partially mediated through STAT3 activation, comparable to the effect of select PBRM1 somatic mutations. 15 DPF3 effect on T-cell-mediated cytotoxic and immunotherapy response Previous studies have suggested that mutations within the SWI/SNF complexes, particularly in PBRM1, could contribute to response to immune checkpoint inhibitor therapy in RCC affected individuals, 77,78 but other studies could not find this association; [79][80][81] confirmation studies are needed. 82 Ex vivo data suggest that PBRM1 mutations are associated with enhanced sensitization to killing by T cells, 83 an effect most likely mediated through mSWI/ SNF complex regulation of chromatin accessibility for INF-g target genes.…”
Section: Dpf3 Changes Chromatin Accessibility Leading To Altered Gene Expressionmentioning
confidence: 99%